Contribution to the study of swine atrophic rhinitis. I. Isolation and identification of the causative agent - ΜΕΝΑΣΕ Ι.; ΣΚΥΡΙΑΝΟΣ Γ.; ΣΕΪΜΕΝΗΣ Α.; ΧΟΝΤΟΥ Α.; ΣΤΟΦΟΡΟΣ Ε. (Journal of the Hellenic Veterinary Medical Society, 2019)
Swine Atrophic Rhinitis, which is the cause of serious problems in the intensive breeding farms, occurs in Greece with the typical symptoms on piglets from their first days of life. The experiments performed on the isolation and identification of the principal causative agent, i.e. Bordetella bronchiseptica from pathologic material coming from affected piglets of two farms are described in this study. Although Pasteurella multocida is known to be the principal pathogenic microrganism which burdens the manifestation of the desease, was not isolated from any of the cases gone through.